A transaction case analysis of the development of generation rights trading and existing shortages in China. (February 2021) - Zhao, Wenhui; Zhang, Jiuyang; Li, Ruan; Zha, Ruiming
Abstract: In the transition from a planned economy to a market economy of power sector reform in China, generation rights trading (GRT) as a mainly method to solve the problem of renewable energy curtailment. GRT presents significant differences from other countries' electricity derivatives such as electricity swap in subject matter, pricing mechanisms, etc. Electricity swap has been analyzed in many research work but few studies have been published on China's GRT policy system, our work can offer a new perspective to show traits and policy characteristics of GRT to fill this gap for other researchers. As a primary innovation point, this paper introduces the basic concept, development history, transaction mode, the policy system of GRT and the main differences between GRT and electricity swap in US electricity financial derivatives market are compared. Case analysis as research method is widely used in this paper, origin and components of transaction prices of GRT in Shanghai is investigated. This research shows that GRT is concentrated in regions which have rich natural resources or high demand of electricity and other energy of China and mainly dominated by the government, while GRT can improve the operating profits for renewable energy power plants and reduce renewable energy curtailment, many problems still exist such as unreasonable benefits distribution, lacking market adjustment mechanisms compare with electricity swap, and exorbitant price of coal compared with electricity price. Highlights: Differences between China's GRT and other countries' electricity swap. The government plays a leading role in trading. The annual trading volume fluctuates sharply and concentrated in eastern region. The grid gets most of the trading profits, generator and consumer only gain a few. Optimize evaluation method, adjusting electricity price can promote GRT.